Handbook of Cancer Survivorship (Springer International Publishing, 2018)
The timely revision of this authoritative handbook gives a wide range of health care providers practical insights and strategies for treating cancer survivors' long-term physical and mental health issues and promoting healthy lifestyle habits. Details of new and emerging trends in research and practice enhance readers' awareness of issues faced by survivors so they may better detect, monitor, intervene in, and if possible prevent distressing conditions and potentially harmful outcomes. Of particular emphasis are different models of care that may be applicable to diverse clinical settings around the world. New or updated chapters cover major challenges to survivors' quality of life and options for health care delivery across key life domains, including: · Adaptation and coping post-treatment. · Problems of aging in survivorship, including disparities and financial hardship. · Well-being concerns including physical activity, weight loss, nutrition, and smoking cessation. · Core functional areas such as work, sleep, relationships, and cognition. · Large-scale symptoms including pain, distress, and fatigue. · Models of care including primary care and comprehensive cancer center. · International perspectives · PLUS, insights about lessons learned and challenges ahead. With survivorship and survivorship care becoming an ever more important part of the clinical landscape, the Second Edition of the Handbook of Cancer Survivorship is an essential reference for oncology specialists, primary care providers, mental health professionals, rehabilitation providers, as well as public health specialists, epidemiologists and policy makers. .